Women's status and experiences of mistreatment during childbirth in Uttar Pradesh: a mixed methods study using cultural health capital theory. Issue 1 (December 2016) - Sudhinaraset, May; Treleaven, Emily; Melo, Jason; Singh, Kanksha; Diamond-Smith, Nadia
Abstract Background Mistreatment of women in healthcare settings during childbirth has been gaining attention globally. Mistreatment during childbirth directly and indirectly affects health outcomes, patient satisfaction, and the likelihood of delivering in a facility currently or in the future. It is important that we study patients' reports of mistreatment and abuse to develop a deeper understanding of how it is perpetrated, its consequences, and to identify potential points of intervention. Patients' perception of the quality of care is dependent, not only on the content of care, but importantly, on women's expectations of care. Methods This study uses rich, mixed-methods data to explore women's characteristics and experiences of mistreatment during childbirth among slum-resident women in Uttar Pradesh, India. To understand the ways in which women's social and cultural factors influence their expectations of care and consequently their perceptions of respectful care, we adopt a Cultural Health Capital (CHC) framework. The quantitative sample includes 392 women, and the qualitative sample includes 26 women. Results Quantitative results suggest high levels of mistreatment (over 57 % of women reported any form of mistreatment). Qualitative findings suggest that lack of cultural health capital disadvantages patients in their patient-provider relationships, and that women use resources to improve care they receive. Participants articulated how providers set expectations and norms regarding behaviors in facilities; patients with lower social standing may not always understand standard practices and are likely to suffer poor health outcomes as a result. Of importance, however, patients also blame themselves for their own lack of knowledge. Conclusions Lack of cultural health capital disadvantages women during delivery care in India. Providers set expectations and norms around behaviors during delivery, while women are often misinformed and may have low expectations of care.